The Opportunities for Professional Growth When Using Knowledge of Students’ Prior Science Ideas in the Teaching of Evolution and Genetics: A Self-Study - Tshuma, Tholani; Nyamupangedengu, Eunice (Research in Social Sciences and Technology- OpenED Network, 2025)
This inquiry sought to investigate the opportunities and potential challenges of engaging in a self-study approach as a strategy for enhancing professional growth during my teaching of the topic of evolutionary genetics to 24 twelfth-grade students. I had, for many years, experienced pedagogical deficits and shortcomings when teaching evolutionary genetics despite my professional knowledge from my teacher training. I always struggled to a) represent this content in ways that make it comprehensible to my students, b) motivate my students to accept this topic, and c) address students’ misconceptions. Vygotsky’s social constructivism of knowledge and the idea of pedagogical reasoning and action as propounded by Shulman were the key theoretical lenses that guided this inquiry. Collected data included pre- and post-intervention data, students’ conceptions of evolutionary genetics ideas, lesson transcripts, my reflections, pedagogical actions and reasoning during my teaching, and notes on collaborative activities with critical friends. The collected data was analysed from a quantitative and qualitative approach. Thematic analysis for emerging themes was done from a deductive to inductive data analysis approach. This study established that through the idea of opening up for professional feedback from critical friends, one ought to make one’s pedagogical reasoning and actions public. This opening up makes one ‘vulnerable’ to severe criticism or ‘attack' by critical friends. However, despite this setback, it offers unlimited professional growth opportunities beyond one’s personal biases, interpretations, and teacher training expertise on key issues of practice. The ‘negative’ and positive critiques from others are powerful critical reflection points for enhancing professional development. However, through engaging in open feedback collaborative sessions, a practitioner experiences internal tensions between the 'inner egoistic voice' and the probing 'outer voice'. Thus, the ability to objectively reconcile one’s inner voices in the wake of the usually unfriendly outer voices is a crucial starting point for one to realise professional growth as a practitioner.